Regional asymptotic stability analysis for discrete-time delayed systems with saturation nonlinearity - Lee, S. M.; Kwon, O. M.; Park, Ju H. (Nonlinear dynamics, 2012)
This paper presents a novel method for asymptotic stability analysis of discrete-time systems with state delay and saturation nonlinearity. Based on Lyapunov functional and LMI (linear matrix inequality) framework, new stability criteria are derived in terms of LMIs by using some properties of the saturation nonlinearity. The criteria can be applied to the global and regional stability. Numerical examples are given to verify the theoretical result of the proposed method.